Alteration of white-rot basidiomycetes cellulase and xylanase activities in the submerged co-cultivation and optimization of enzyme production by Irpex lacteus and Schizophyllum commune. (October 2017) - Metreveli, Eka; Kachlishvili, Eva; Singer, Steven W.; Elisashvili, Vladimir
Highlights: White-rot basidiomycetes are promising sources of cellulases and xylanases. Irpex lacteus and Schizophyllum commune showed compatible interaction. Availability of carbon source determined outcomes of interspecific interaction. Co-culture conditions optimization improved hydrolases production. Synergistic enzyme preparation exhibited 11% higher hydrolysis of biomass. Abstract: Mono and dual cultures of four white-rot basidiomycete species were evaluated for cellulase and xylanase activity under submerged fermentation conditions. Co-cultivation of Pycnoporus coccineus or Trametes hirsuta with Schizophyllum commune displayed antagonistic interactions resulting in the decrease of endoglucanase and total cellulase activities. In contrast, increases in cellulase and xylanase activity were revealed through the compatible interactions of Irpex lacteus with S. commune . Co-cultivation conditions were optimized for maximum enzyme production by I. lacteus and S. commune, the best producers of cellulase/xylanase and β-glucosidase, respectively. An optimized medium for the target enzyme production by the mixed culture was established in a laboratory fermenter yielding 7 U/mL total cellulase, 142 U/mL endoglucanase, 104 U/mL xylanase, and 5.2 U/mL β-glucosidase. The dual culture approach resulted in an enzymatic mixture with 11% improved lignocellulose saccharification potential compared to enzymes from a monoculture of I. lacteus .